Rethinking Networking for "Five Computers" - Renganathan, Sundararajan; Padmanabhan, Venkat; Nambi, Akshay (ACM HotNets, 2018)
T. J. Watson's apocryphal statement about there being a market for only "five computers" has, in a sense, come true with the rise of cloud computing and the dominance of a handful of "mega-computers" in terms of Internet traffic volume. However, network protocols and operation over the Internet have, for the most part, remained wedded to the old world, with individual hosts operating autonomously. We argue that this is suboptimal and that the time has come to revisit networking in the world of "five computers." We consider various networking functions, including specifically congestion control and network diagnosis, and provide an indication of the potential benefits of a new coordinated approach and sketch out an approach to realizing these benefits.